2019
DOI: 10.3390/s19122808
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Electroencephalographic Recordings Obtained with a Consumer-Grade, Single Dry Electrode, Low-Cost Device: A Comparative Study

Abstract: The functional validity of the signal obtained with low-cost electroencephalography (EEG) devices is still under debate. Here, we have conducted an in-depth comparison of the EEG-recordings obtained with a medical-grade golden-cup electrodes ambulatory device, the SOMNOwatch + EEG-6, vs those obtained with a consumer-grade, single dry electrode low-cost device, the NeuroSky MindWave, one of the most affordable devices currently available. We recorded EEG signals at Fp1 using the two different devices simultane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 52 publications
1
40
0
2
Order By: Relevance
“…To our knowledge, this is the first study to use a mobile single-channel EEG device to monitor TMo surgeries; for this reason, there is no comparative method. It should be viewed as an exploratory study with highly interesting points that may direct the development of a new device for identifying biological markers to explore surgical stress in oral surgery; NBSKeeg, used in this research, shows fair validity and reliability, and it has been employed by several clinical studies [ 10 11 12 13 23 24 25 26 ]. Clinical modifications of the initial protocol, such as expanding the EEG monitoring period to cover the full surgery and clinically time-controlling the events of the trans-surgical development, could also be an interesting approach.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To our knowledge, this is the first study to use a mobile single-channel EEG device to monitor TMo surgeries; for this reason, there is no comparative method. It should be viewed as an exploratory study with highly interesting points that may direct the development of a new device for identifying biological markers to explore surgical stress in oral surgery; NBSKeeg, used in this research, shows fair validity and reliability, and it has been employed by several clinical studies [ 10 11 12 13 23 24 25 26 ]. Clinical modifications of the initial protocol, such as expanding the EEG monitoring period to cover the full surgery and clinically time-controlling the events of the trans-surgical development, could also be an interesting approach.…”
Section: Discussionmentioning
confidence: 99%
“…Electroencephalography (EEG) is one of the most commonly used techniques for neurological and psychological assessments, and it has been performed with highly sensitive time-consuming assembly and expensive electronic devices [ 10 11 12 ]. Advances in technology have facilitated the production of mobile and low-cost EEG apparatus and the development of brain-computer interfaces, which, in turn, enable EEG recordings in previously impossible situations [ 10 11 12 ], such as driving, cycling, and undergoing surgery under local anesthesia. Rieiro et al (2019) [ 12 ] compared this form of EEG to medical-grade EEG and observed a substantial agreement between the equipment recordings, indicating that the metrics from both were significantly correlated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Electroencephalography EEG, since it's first introduction early in the 20th century, has been an essential and the most common neurophysiological device to monitor and study the electrical and functional activity of the brain [17]. EEG is a commonly used non-invasive tool to track and record the electrical field potentials captured by electrodes placed on the patient scalp.…”
Section: Technical Aspects Of Electroencephalographymentioning
confidence: 99%
“…Considering the EEG being useful for direct reflections of humans’ emotional states with relatively low costs and simplicity, Kim et al [ 28 ] reviewed the computational methods that have been developed to deduct EEG indices of emotion, to extract emotion-related features, or to classify EEG signals into one of many emotional states; mentioned that EEG-based emotional state estimation requires well designed computational methods to extract information from complex and noisy multichannel EEG data; and proposed the use of sequential Bayesian inference to estimate the continuous emotional state in real time. Furthermore, Rieiro et al [ 29 ] conducted an in-depth comparison of the EEG recording qualities of a medical-grade device, the SOMNOwatch + EEG-6, and a consumer-grade device, the NeuroSky MindWave Mobile [ 30 ]; and revealed the fact that though the MindWave Mobile is noise-limited, it provides stable recordings even through long time periods with its data being of adequate quality compared to that of conventional wet electrode EEG devices, except for a potential calibration error and spectral differences at low frequencies.…”
Section: Related Studiesmentioning
confidence: 99%